The İnfluence of İnnovative Corporate Social Responsibility Activities on Employees’ Job Satisfaction and Employee Commitment - Mrunali Ahirrao (International Journal of Advanced Science and Technology, 2020)
The aim of this research paper is to review and critically analyze the importance of innovative CSR activities in boosting employees’ commitment and employees’ job satisfaction level. CSR is one of the standard practices that focus on creating a shared value amongst all stakeholders of an organization, especially its employees. This paper will establish a positive relationship between innovative CSR and employees of an organization. In order to understand genuine commitment of organizations towards CSR sustainability, the author has studied the impact on employee engagement levels of CSR oriented organizations. After analyzing the available information, the author has arrived at significant factors that act as mediators to form this positive relationship benefitting organizations as a whole such as organizational image. In this context, this paper is an attempt to contribute by doing empirical research on CSR and interrogate and investigate the underlying mechanisms that bring together and link CSR activities with employee behavior impacting organizational performance such as job satisfaction and employee commitment. The aftermath effect of CSR on the vital stakeholders such as consumers is largely studied to increase the profitability of the firm. However, the study of employees’ performance and its correlation with CSR is understudied and the relation between them is fairly unclear. It is also one of the major reasons contributing toward employee loyalty, in turn increasing employee and satisfaction and thus, profitability.